2012
DOI: 10.1177/1403494811435494
|View full text |Cite
|
Sign up to set email alerts
|

Educational inequalities in disability pensioning – the impact of illness and occupational, psychosocial, and behavioural factors: The Nord-Trøndelag Health Study (HUNT)

Abstract: Illness and occupational, psychosocial, and behavioural factors explained some of the educational inequalities in disability pensioning. However, considerable inequalities remain after accounting for these factors. The higher incidence of disability pensioning in women than men and the small or non-existing educational inequalities in the oldest women calls for a gender perspective in future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
23
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 24 publications
2
23
0
1
Order By: Relevance
“…This explanation has been empirically supported in several studies to a greater or lesser extent (4,(12)(13)(14)(15). Correspondingly, both physical and psychosocial working conditions are considered to be established risk factors for disability pension (16)(17)(18).…”
mentioning
confidence: 67%
See 3 more Smart Citations
“…This explanation has been empirically supported in several studies to a greater or lesser extent (4,(12)(13)(14)(15). Correspondingly, both physical and psychosocial working conditions are considered to be established risk factors for disability pension (16)(17)(18).…”
mentioning
confidence: 67%
“…While a majority of these studies have shown quite similar associations among men and women, a few have shown weaker associations among women (4,6). Studies examining disability pension by type of diagnosis have suggested roughly the same association between education and disability pension for psychiatric diagnoses as for disability pension overall, but not as strong as in the case of musculoskeletal diagnoses (1,7).…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…Socioeconomic differences in DR have been found to be larger among younger than older disability retirees (30). Smaller socioeconomic differences in older age groups may be a consequence of the lower socioeconomic status of people having retired due to disability at a younger age.…”
Section: -64-yearsmentioning
confidence: 99%